Organizational Culture Mapping and Home Industry Performance in Pasuruan Regency: Pemetaan Budaya Organisasi dan Kinerja Industri Rumahan di Kabupaten Pasuruan - Fauzan Bhimantara Yudhie; Rifdah Abadiyah (Universitas Muhammadiyah Sidoarjo, 2022)
This study aimed to investigate the current and expected profile of organizational culture and its effect on employee performance. The research employed a quantitative approach, utilizing the Organizational Culture Assessment Instrument (OCAI) to collect data through a survey. Total sampling and non-probability sampling methods were employed, with 184 respondents participating in the study. The analysis, conducted using IBM SPSS Statistics software (Version 24), revealed a common perception between owners and employees, indicating that the current cultural profile of the organization is dominated by hierarchy and market cultures. However, the desired cultural profile aspired to maximize the presence of hierarchy, market, clan, and adhocracy cultures. Furthermore, the study demonstrated a simultaneous and partial influence of hierarchical culture, market culture, clan culture, and adhocracy culture on employee performance. Among these, the variables of hierarchy culture and clan culture were found to have the most significant impact on IKM performance. These findings emphasize the importance of understanding and shaping organizational culture to enhance employee performance and productivity. Highlights: Current and expected profile of organizational culture: The study explores the current and expected cultural profile of Pia Japanan IKM, identifying the prevailing culture as hierarchy and market, while aiming to maximize hierarchy, market, clan, and adhocracy cultures in the future. Influence on employee performance: The research reveals a significant impact of hierarchical culture, market culture, clan culture, and adhocracy culture on employee performance, with hierarchy culture and clan culture identified as the most influential variables for IKM performance. Quantitative approach and sampling: The study employs a quantitative approach, using the Organizational Culture Assessment Instrument (OCAI) for data collection through a survey. Total sampling and non-probability sampling methods are utilized, with 184 respondents included in the analysis. Keywords: Organizational culture, Hierarchy culture, Market culture, Clan culture, Adhocracy culture.